Gray hat hacking the ethical hacker's handbook - Regalado, Daniel (McGraw-Hill Education, 2015)
This fourth edition explains the enemy's current weapons, skills, and tactics, and offers field-tested remedies, case studies, and ready-to-deploy testing labs. You will learn how to build and launch spoofing exploits with Ettercap and Evilgrade; induce error conditions and crash software using fuzzers; hack Cisco routers, switches, and network hardware; use advanced reverse engineering to exploit Windows and Linux software; bypass Windows Access Control and memory protection schemes; scan for flaws in Web applications; utilize use-after-free technique used in recent zero days; bypass Web authentication; inject your shellcode into a browser's memory using the latest Heap Spray techniques; hijack Web browsers with Metasploit and the BeEF Injection Framework; neutralize ransomware before it takes control of your desktop; dissect Android malware with JEB and DAD decompilers; and find one-day vulnerabilities with binary diffing. --
Includes bibliographical references and index. - Description based on print version record
Keywords: Computer security; Hackers; Hacking; Computer Security; Sécurité informatique; Pirates informatiques; Piratage informatique; Engineering & Applied Sciences; Computer Science; Computing & information technology; Computer networking & communications; Ethical & social aspects of IT; Computer fraud & hacking; Network security; Computers and IT